The Analytic Study of the Shia and Sunni Exegetes’ Opinions about the Verse “لَا یُسْأَلُ عَمَّا یَفْعَلُ وَهُمْ یُسْأَلُونَ” - Ali Reza Tabibi; Ayyub Amraei; Khadijeh Faryadres; Abulfazl Safari (آموزه‌های قرآنی, 2022)
The exegetes have presented different opinions and sometimes in conflict (conflicting) for the exegesis of some verses of the holy Quran. One of these verses is the verse “لَا یُسْأَلُ عَمَّا یَفْعَلُ وَهُمْ یُسْأَلُونَ” which is a state of opposition between opinions from the different aspects. These cases include the linguistic sense (siaq) of the verses, the time of occurrence, I'rab (syntactic analysis), antecedents of pronouns, the content of “ما” in “عَمَّا یَفْعَلُ”, the type of question, why not rebuking (scolding) in “لَا یُسْأَلُ” and why rebuking in “وَهُمْ یُسْأَلُون”. The present research with library method in collecting issues, the documentary method in presenting opinions and the method of the descriptive and qualitative analysis of the content in the evaluation of data has examined and analyzed the opinions of the Quran exegetes in connection with (concerning) the different parts of the verse. The outcomes are some of the opinions for the mentioned aspects are debatable (capable of being reviewed) and the best exegesis for the verse is the lack of the reprimandable request of God Almighty for His possessing and the reprimandable request of goddess for being possessed.